Validation of the family health scale among heterosexual couples: a dyadic analysis - AliceAnn Crandall; Melissa Barlow (BMC, 2022)
Abstract Background The Family Health Scale (FHS) is a recently validated comprehensive measure of family health for use in survey research with the potential to also be used as a clinical measure. However, previous research has only validated the FHS among one member of the family rather than multiple family members. The objective of the study was to examine the psychometric properties of the FHS long- and short-form among married and cohabitating partners (dyads). Method The sample for this study was comprised of 482 married or cohabitating heterosexual couples (dyads) who were parents of a child between the ages of 3-13, heterosexual, and living in the United States. Each member of the dyad completed a survey about his or her perception of family health, personal health, childhood experiences, and demographic characteristics. Confirmatory factor analyses (CFA) were conducted to examine the factor structure. Unidimensional, correlational, and second-order factor structures were examined using responses from both partners. The relationships between family health with individual health and demographic covariates were also examined. Results Women and men reported their family health similarly. The unidimensional factor structure had the best fit for the FHS short-form while either the unidimensional model or the second-order model would be appropriate for the FHS long-form. Household income, individual member mental health, and childhood experiences were associated with family health in the expected direction. Conclusion The results demonstrate that the FHS is a valid and reliable family measure when examining family health among dyads including married and cohabitating heterosexual couples who have children.